DESIGN AND CHARACTERIZATION OF AN ULTRA-LOW POWER INTERFACE CIRCUIT FOR OPTICAL SENSORS - YOHANNES, ISRAEL (2013)
Sensors are one of the most ubiquitous devices in our day to day life. The ever increasing demand for insitu environmental monitoring has created a continuing research endeavor to produce a low-cost, low power, fast sensor systems. Optical sensors are preferred for various applications due to their non-intrusive nature and are commonly used to monitor the environment. Dedicated interface electronics are needed to interpret the output ofthese sensors accurately into a usable form to a user or subsequent systems. In this work, an interface circuit arrhitppfnre for nptirnl r^n-.nr is proposed that is suitable for integration in a single chip.